UPDATES ON MOLECULAR MARKERS LINKED TO POTATO VIRUS Y (PVY) RESISTANCE GENES IN POTATO - Mangal, Vikas; Sood, Salej; Raigond, Baswaraj; Dalamu, Dalamu; Thakur, Ajay Kumar; Kumar, Vinod; Singh, Baljeet; Kumar, Ashwani; Singh, Rajender; Bhardwaj, Vinay (Potato Journal, 2022)
Potato is the leading non-grain food product in the world and stands third important food crop after wheat and rice. It is a future crop for ensuring food security in the developing world but it is affected by several biotic and abiotic factors which reduce the total yield. Among the biotic stresses, PVY is also the worldwide problem in potato causing serious damage. PVYO, PVYN, and PVYC are the main strains of PVY causing losses to potato cultivation. The complex strains of the PVY are responsible for different foliar and tuber symptoms in potato. The recombination between different strains creates new harmful strains (PVYNTN, PVYN:O, PVYN-Wi) which from the last many years becomes a serious problem. Two types of resistance genes (HR and ER) are mapped on different potato species for PVY strains. Extreme resistance genes are reported in S. tuberosum gp. andigenum (Ryadg), S. stoloniferum (Rysto and Ryfsto) and S. chacoense (Rychc). Likewise, hypersensitive response (HR) genes are found in S. tuberosum (Nytbr, Ny-1, and Ny-2), S. sparsipilum (Ncspl), and Sarpo Mira (Ny-Smira). Ryadg and Ny-2 genes were reported on chromosome no XI, Rysto and Ryfsto on chromosome no XII, Nytbr and Ncspl chromosome no IV, and Rychc, Ny-1, and Ny-Smira on chromosome no IX. Till now various molecular markers (AFLP, SCAR, RAPD, STS, CAPS, and RGL) linked to different PVY resistance genes are reported in various populations. Marker-based selection in the breeding programme can hasten the breeding process and reduce dependency on taking up chemical or other management practices.